Case Report : Diagnosis dan Tatalaksanan Pasien Laki-Laki 40 Tahun dengan Kolelitiasis di Rumah Sakit Cut Meutia Aceh Utara - Nur Rahmi; Hendra Kastiaji (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Cholelithiasis or gallstones are pieces of solid material that form in the gallbladder. The prevalence rate of cholelithiasis in developed countries is around 10-15% of the adult population, with the prevalence of cholesterol cholelithiasis. A 40-year-old man came to the emergency room of Cut Meutia Hospital with complaints of pain in the upper right abdomen since 3 weeks ago. The results of the abdominal physical examination found pressure pain in the hypochondrium dextra, murphy sign (+).Based on the examination of bile ultrasound and the results of gallbladder stone multiple. Based on anamnesis, physical examination and elongation examination of the patient was diagnosed with Cholelithiasis + Internal Hemorrhoids Grade I. Surgical management was carried out in the form of laparoscopy, cholecystectomy and postoperative therapy in the form of bed rest, postoperative wound healing, postoperative mobilization and a diet high in fiber and protein and fatty lace diet.